2005
DOI: 10.1007/s10620-005-2456-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Feasibility of Three Rapid Urease Tests in the Diagnosis of Helicobacter pylori Infection

Abstract: Rapid urease tests (RUTs) are a fast, accurate, and inexpensive method to diagnose H. pylori infection in the endoscopy suite. Of these, the CLO test is both common and widely used. The aim of our study was to evaluate the accuracy and positive reaction times of two new rapid urease tests (ProntoDry and HpONE) in comparison with the CLO test. Fifty-one patients (26 men, 25 women; mean age, 52.4 years) were included in this study, and all underwent esophagogastroduodenoscopy (EGD). None of the patients had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…Among the various existing stains, one of the most recommended because of its simplicity and low cost is Giemsa staining (52,115,169,175) . Histological diagnosis and the urease test may show up to 95% sensitivity depending on the quality of material and expertise of the examiner (137,197) . Antisecretory drugs (H 2 receptor antagonists of histamine and proton pump inhibitors) and/or previous use of bismuth or antibiotics, by reducing the bacterial load, affect the accuracy of the urease test, so, whenever possible, an interval of two and 4 weeks respectively between suspending the drugs and the test is recommended (83,132) .…”
Section: Statementmentioning
confidence: 99%
“…Among the various existing stains, one of the most recommended because of its simplicity and low cost is Giemsa staining (52,115,169,175) . Histological diagnosis and the urease test may show up to 95% sensitivity depending on the quality of material and expertise of the examiner (137,197) . Antisecretory drugs (H 2 receptor antagonists of histamine and proton pump inhibitors) and/or previous use of bismuth or antibiotics, by reducing the bacterial load, affect the accuracy of the urease test, so, whenever possible, an interval of two and 4 weeks respectively between suspending the drugs and the test is recommended (83,132) .…”
Section: Statementmentioning
confidence: 99%
“…The results showed that the sensitivity and specificity of the test were 84.6% and 100%, respectively (27). Tseng et al (28) compared three different RUTs and found that the sensitivity of the tests was 86.2-93%, while the specificity was 100%. In concordance with medical literature, in our study, the sensitivity of the RUT was 92.86%, while the specificity was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The urease activity of the dental biofilm was measured by the use of a modified rapid urease test [18,22,23] in interproximal plaque samples from 4 interproximal sites (mesial aspect of 11, 26, 36, and 41). The urea broth used consisted of urea (10%) in distilled water and 0.02 g/L of phenol red; the pH was adjusted to 6.8.…”
Section: Methodsmentioning
confidence: 99%